Different Effects of Bench Dip and Wheelbarrow Training on Swimming Speed in 25 Meters Freestyle KU IV Gading Swimming Club in 2022 - Mahmuddin; Lutfia Novtriana Pasaribu (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study was to determine the significant effect of the bench dip exercise on the swimming speed of the 25 meter freestyle KU IV Gading Swimming Club in 2022, to determine the significant effect of the Wheelbarrow exercise on the swimming speed of the 25 meter freestyle KU IV Gading Swimming Club in 2022 , and to find out how much difference the bench dip and wheelbarrow exercises have to the swimming speed of the 25 meter freestyle at KU IV Gading Swimming Club in 2022. The research was conducted at the swimming club Gading Swimming Club. In the swimming pool of Villa Gading Mas, the Villa Gading Mas complex, Jl Bajak II, Harjosari II Village, Medan Amplas District. This research will be carried out for 6 weeks and will take place from 09 January 2023 to 17 February 2023. The number of samples in this study amounted to 10 people. This research is a type of experimental research. Research instrument to collect data with a 25 meter swimming speed test. The conclusion of the results of the first hypothesis analysis from the pre-test data and post-test data is that there is a significant effect of Bench Dip training on the 25-meter freestyle swimming speed of KU IV Gading Swimming Club athletes in 2022. In the results of the second hypothesis analysis there is a significant effect on Wheelbarrow exercise on the 25-meter freestyle swimming speed of KU IV Gading Swimming Club athletes in 2022. Furthermore, the results of the third hypothesis analysis show that the Bench Dip exercise has no significantly greater effect than the Wheelbarrow exercise on increasing the 25-meter freestyle swimming speed of KU IV Gading Swimming athletes. Clubs of the Year 2022.